Optical Imaging: A General In Situ Growth Strategy of Designing Theranostic NaLnF4@Cu2−xS Nanoplatform for In Vivo NIR‐II Optical Imaging Beyond 1500 nm and Photothermal Therapy (Adv. Therap. 6/2019). Issue 6 (7th June 2019) - Jiang, Mingyang; Liu, Hongrong; Zeng, Songjun; Hao, Jianhua
Abstract : In article number1800153, Songjun Zeng, Jianhua Hao and co‐workers demonstrate a general in‐situ growth strategy for designing integrative NaLnF4 @Cu2-x S theranostic nanoprobes with a combination of efficient NIR‐II emission and high performance photothermal therapy (PTT). NIR‐II Optical imaging guided small tumor detection, non‐invasive in vivo brain vessel imaging and PTT of tumors are achieved, providing a new opportunity for designing highly sensitive theranostic nanoprobes by integrating NIR‐II imaging with PTT.